"The United States Stands Ready to Be of Assistance": On the Politics and Humanitarianism of Natural Disaster. Issue 4 (1st October 2016) - Nelson, Travis
Abstract : This article asks how American understandings of foreign natural disaster have evolved over time. Are the political and humanitarian concerns surrounding disaster and disaster aid radically different now from what they were a century ago? Through an analysis of presidential statements and major newspaper editorials following foreign natural disaster, I find that there has indeed been significant change. Notions of post-disaster humanitarianism have broadened significantly, with, among other things, disaster aid going from being discussed as an act of charity to an understood responsibility. Furthermore, the political side of foreign natural disaster has moved beyond the political effects of disaster itself to include the political causes of "natural" disaster and the political causes and effects of disaster aid. These and other patterns are used to consider the relationship between politics and humanitarianism more generally.